2018
DOI: 10.1088/1741-2552/aae4b9
|View full text |Cite
|
Sign up to set email alerts
|

Online classification of imagined speech using functional near-infrared spectroscopy signals

Abstract: Objective. Most brain–computer interfaces (BCIs) based on functional near-infrared spectroscopy (fNIRS) require that users perform mental tasks such as motor imagery, mental arithmetic, or music imagery to convey a message or to answer simple yes or no questions. These cognitive tasks usually have no direct association with the communicative intent, which makes them difficult for users to perform. Approach. In this paper, a 3-class intuitive BCI is presented which enables users to directly answer yes or no que… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 53 publications
1
24
1
Order By: Relevance
“…In line with this, it has been demonstrated that HbO signal is more robust than HbR for motor imagery specific activation (Mihara et al, 2012). Likewise, Rezazadeh Sereshkeh et al (2018) reported that HbO signals yielded the highest accuracies in their 3-class BCI using imagined speech, and Hwang et al (2016) reported that HbO features yield more discriminative information than HbR features in 2-class communication.…”
Section: Communication Accuracymentioning
confidence: 60%
See 3 more Smart Citations
“…In line with this, it has been demonstrated that HbO signal is more robust than HbR for motor imagery specific activation (Mihara et al, 2012). Likewise, Rezazadeh Sereshkeh et al (2018) reported that HbO signals yielded the highest accuracies in their 3-class BCI using imagined speech, and Hwang et al (2016) reported that HbO features yield more discriminative information than HbR features in 2-class communication.…”
Section: Communication Accuracymentioning
confidence: 60%
“…However, to our knowledge, no study has tested the use of two mental tasks directly in a communication experiment. In a recent study, participants imagined different mental speech content for answering yes/no questions intuitively, i.e., imagining saying "yes" or "no" repeatedly (Rezazadeh Sereshkeh et al, 2018). An average accuracy of 64.1% was attained over two experimental sessions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, linear discriminant analysis (LDA) classifier has been most widely used for NIRS-BCIs because of its excellent performance reflected by both a fast learning rate and a good classification performance (Holper and Wolf, 2011;Power et al, 2011Power et al, , 2012aSchudlo and Chau, 2014;Hong et al, 2015;Shin et al, 2016Shin et al, , 2018aHong and Khan, 2017). In applying the classifier, dimension reduction or feature selection methods are generally employed because the number of NIRS feature vectors is usually larger than that of training datasets and this might degrade the BCI performance due to the poor empirical sample covariance Sereshkeh et al, 2019). Regularization with a shrinkage parameter can be another option to alleviate the adverse effect of the large dimensionality (Fazli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%